THE INTERNATIONAL EVENT “DAYS OF MOUNTAIN WATER”, TETEVEN, BULGARIA, MICROBIOLOGICAL AND PHYSICOCHEMICAL RESEARCH OF MOUNTAIN SPRING WATER - IGNATOV, IGNAT; IGNATOV, ALEXANDER I.; ANGELCHEVA, MARIANA; ANGUSHEV, IVAN (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
In Bulgaria there are the following mountains – Stara Planina (Balkan), Rila, Pirin, Rodope etc. The name of the Balkan Peninsula is from the old name of the mountain Stara Planina – Balkan. In Bulagria there are 139 peaks more than 2000 m above sea level. The biggest peak in Balkan Peninsula is Mousala (2925 m). Teteven municipally has big part of Stara planina mountain with the highest peak Vezhen (2198 m). The event “Days of mountain water” is one of a kind in Bulgaria. It takes place on 11th June and lasts for several days in the Municipality of Teteven, Bulgaria. Its beginning dates from 2010, and it is a joint undertaking between Ignat Ignatov, Scientific Research Center of Medical Biophysics and Municipality of Teteven, Bulgaria. The event is connected with research of microbiological and physicochemical parameters of mountain spring waters from Municipality of Teteven, Bulgaria. The applied spectral method is „NES“. The analyses show the optimum quantity among the minerals of Calcium (Са2+), Magnesium (Mg2+), Potassium (K+), Sodium (Nа+), Manganese (Mn2+) and Zinc (Zn2+) that provide the right balance in the human body for health and longevity. Considered is the history of the event and what is achieved by the organizers. The emphasis is on the main objectives set out by the event, and the accomplished tasks for its successful delivering. Representatives of 15 states have participated in it – Bulgaria, Austria, Germany, Switzerland, Russia, USA, France, Israel, Czech Republic, Denmark, Turkey, Greece, Hungary and Serbia. A survey was conducted regarding the event “Days of mountain water” in the Facebook group “Teteven Balkan”. 66 people responded on a random basis. The aim of the survey was the people to estimate how useful stay in Teteven municipality is. In the present article are listed in more detail the natural assets of municipal area of Teteven, located in “Fore-Balkan” in the central part of Stara planina Balkan range. The possibilities are shown for development of tourism in the region, its particular characteristics and specific features. Analyzed are the water resources, the mountain water as a factor for health and longevity. The information helps for development of tourism in the region. Described are the springs and fountains of mountain water in Teteven and its surrounding municipal areas. It is conducted quantitative and qualitative analysis of the chemical and physical parameters of the springs. On six of the springs are placed information signs about the chemical composition, physical parameters and properties relating to health.